2003
DOI: 10.1038/sj.eye.6700376
|View full text |Cite
|
Sign up to set email alerts
|

Does frequency doubling technology perimetry reliably detect neurological visual field defects?

Abstract: Aim To determine the ability of frequency doubling technology (FDT) perimetry to detect visual field defects of neurological origin. Methods A total of 15 eyes of nine patients who all had complete hemianopias or quadrantanopias underwent the FDT 20-5 screening mode test and Humphrey 24-2 SITA Fast visual field test (HFA). The FDT results were scored according to the number of abnormal test locations (out of a maximum of 4) in each affected quadrant. FDT locations showing a defect of Po2% were considered abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Recent developments have led to new rapid methods of screening VF. The best known of these is frequencydoubling perimetry, which compares well with conventional VF testing for the detection of glaucoma (Allen et al, 2002;Tatemichi et al, 2002), but is less effective at detecting rarer VF defects from neurological causes (Fong et al, 2003). However, other relatively simple approaches have also shown promise (Schiefer et al, 1996).…”
Section: Community Centresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments have led to new rapid methods of screening VF. The best known of these is frequencydoubling perimetry, which compares well with conventional VF testing for the detection of glaucoma (Allen et al, 2002;Tatemichi et al, 2002), but is less effective at detecting rarer VF defects from neurological causes (Fong et al, 2003). However, other relatively simple approaches have also shown promise (Schiefer et al, 1996).…”
Section: Community Centresmentioning
confidence: 99%
“…, 2002; Tatemichi et al. , 2002), but is less effective at detecting rarer VF defects from neurological causes (Fong et al. , 2003).…”
mentioning
confidence: 99%
“…When different diagnostic criteria were used, however, sensitivity was much poorer, ranging from 40% to 60%. Fong et al 29 concluded that the FDT screening strategy failed to identify hemianopic and quadrantanopic VF defects in more than half of the 15 eyes studied. Our study, however, indicates that the presence of one abnormal point depressed <5% constitutes a very sensitive and specifi c criterion for the diagnosis of DON.…”
Section: Discussionmentioning
confidence: 99%
“…29 While the HFA is the gold standard in perimetry, frequency-doubling technology (FDT) is also popular. The first genera-tion FDT perimeter of Welch Allyn was not sufficiently sensitive to reliably detect hemianopic and quadrantopic visual field defects [30][31][32][33] but the second generation FDT perimeter (Humphrey Matrix) has an improved sensitivity. The HFA is still considered more sensitive than the Matrix in detecting neurological hemianopias.…”
Section: Visual Fieldsmentioning
confidence: 99%